1994
DOI: 10.1159/000108559
|View full text |Cite
|
Sign up to set email alerts
|

Silent Brain Infarcts

Abstract: Silent brain infarcts are infarcts found by neuroimaging or necropsy without a history of stroke. The symptoms may have been unrecognized, forgotten by the patient, or ischemic symptoms may have been only transient. Silent infarcts are common. Infarcts are found on computed tomography (CT) in about 15% of patients with asymptomatic carotid artery lesions. Cerebral infarcts with transient signs (CITS) are noted on CT in about 25% of patients with spells of transient monocular blindness, and a comparable percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…1 SBI is frequently seen on MRIs in healthy elderly people. The prevalence of these asymptomatic lesions increases with age from Ϸ5% at 60 years of age to 35% at 90 years of age.…”
Section: S Ilent Brain Infarction (Sbi) Is Defined As a Cerebralmentioning
confidence: 99%
“…1 SBI is frequently seen on MRIs in healthy elderly people. The prevalence of these asymptomatic lesions increases with age from Ϸ5% at 60 years of age to 35% at 90 years of age.…”
Section: S Ilent Brain Infarction (Sbi) Is Defined As a Cerebralmentioning
confidence: 99%
“…57 None of the prospective studies on consecutive patients with ischemic stroke reported multivariate analysis accounting for collinearity between features related to silent infarcts 2 ' 3 -6 ' 7 except a recent study 1 in which different index-stroke subtypes were not distinguished. Although predominant in all of our four index-stroke subgroups, silent small deep infarcts were significantly more frequent in first-ever lacunar stroke.…”
mentioning
confidence: 99%
“…These findings suggest a similarity in the type of underlying mechanism in symptomatic and silent infarcts: small-vessel vasculopathy in most small deep infarcts and cardiogenic embolism or large-vessel thromboembolism in territorial infarcts. 57 Some patients may suffer from both because silent small infarcts are common among stroke patients with cardiogenic or large-vessel thromboembolism. This may reflect hypertension-related small-vessel vasculopathy because, other than age, hypertension was the only risk factor significantly associated with silent small deep but not territorial infarcts.…”
mentioning
confidence: 99%
“…Furthermore, several recent studies showed that dementia after stroke does not necessarily appear to have "typical" vascular features, such as acute onset. In the present study we assessed the predictive value of SBI in relation to the development of cognitive decline in patients after what clinically appeared to be their firstever ischemic stroke [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%